Affinities of dihydrocodeine and its metabolites to opioid receptors - Schmidt, Helmut; Vormfelde, Stefan V.; Klinder, Klaus; Gundert-Remy, Ursula; Gleiter, Christoph H.; Skopp, Gisela; Aderjan, Rolf; Fuhr, Uwe (Pharmacology & toxicology, 2002)
Dihydrocodeine is metabolized to dihydromorphine, dihydrocodeine-6-O-, dihydromorphine-3-O- and dihydromorphine-6-O-glucuronide, and nordihydrocodeine. The current study was conducted to evaluate the affinities of dihydrocodeine and its metabolites to μ-, δ- and κ-opioid receptors. Codeine, morphine, d,l-methadone and levomethadone were used as controls. Displacement binding experiments were carried out at the respective opioid receptor types using preparations of guinea pig cerebral cortex and the specific opioid agonists [3H]DAMGO (μ-opioid receptor), [3H]DPDPE (δ-opioid receptor) and [3H]U69,593 (κ-opioid receptor) as radioactive ligands at concentrations of 0.5, 1.0 and 1.0 nmol/l, respectively. All substances had their greatest affinity to the μ-opioid receptor. The affinities of dihydromorphine and dihydromorphine-6-O-glucuronide were at least 70 times greater compared with dihydrocodeine (Ki 0.3 μmol/l), whereas the other metabolites yielded lower affinities. For the δ-opioid receptor, the order of affinities was similar with the exception that dihydrocodeine-6-O-glucuronide revealed a doubled affinity in relation to dihydrocodeine (Ki 5.9 μmol/l). In contrast, for the κ-opioid receptor, dihydrocodeine-6-O- and dihydromorphine-6-O-glucuronide had clearly lower affinities compared to the respective parent compounds. The affinity of nordihydrocodeine was almost identical to that of dihydrocodeine (Ki 14 μmol/l), whereas dihydromorphine had a 60 times higher affinity. These results suggest that dihydromorphine and its 6-O-glucuronide may provide a relevant contribution to the pharmacological effects of dihydrocodeine. The O-demethylation of dihydrocodeine to dihydromorphine is mediated by the polymorphic cytochrome P-450 enzyme CYP2D6, resulting in different metabolic profiles in extensive and poor metabolizers. About 7% of the caucasian population which are CYP2D6 poor metabolizers thus may experience therapeutic failure after standard doses.
Gesehen am 28.04.2021